Hydrodynamic characteristics and geometric properties of plunging and spilling breakers over impermeable slopes. (July 2016) - Alagan Chella, Mayilvahanan; Bihs, Hans; Myrhaug, Dag; Muskulus, Michael
Highlights: Numerical modeling of breaking waves. Validation of numerical model with experimental data. Hydrodynamic characteristics of breaking waves. Wave profile asymmetry properties of breaking waves. Wave breaking process over a sloping seabed. Abstract: The two-phase flow CFD model REEF3D has been used for modeling waves breaking over a sloping seabed for a spilling and a plunging breaker. This model is based on Reynolds-averaged Navier–Stokes (RANS) equations with the level set method (LSM) for the free surface and k – ω model for turbulence. First, the characteristics and geometric properties of plunging breaking waves with different offshore wave steepnesses over slopes are examined and discussed. The study further explores the hydrodynamic characteristics of spilling and plunging breakers in terms of the wave height evolution and attenuation, horizontal and vertical velocity, free surface profile evolution, and the geometric properties during the development of the breaking process. The numerical results show a good agreement with experimental data in terms of free surface elevation, horizontal and vertical velocity, wave envelope and turbulent intensity for the spilling and plunging breakers. Results of numerical simulations describing the physical flow characteristics such as the formation of the forward overturning water jet, air pocket, splash-up, and the secondary wave during the breaking process are presented for both cases. For both cases, the physical flow process is found to have similar flow features, but the breaking process occurs at significantly different scales.